Edenville : a novel - Rebelein, Sam (William Morrow an imprint of HarperCollins Publishers, 2023)
"Sam Rebelein's debut Edenville is an unsettling, immersive, and wildly entertaining read for fans of Paul Tremblay and Stephen Graham Jones"--